Addressing Infrastructure and Connectivity Challenges to Unlock Karnali Province’s Economic Potential: A Pathway to Sustainable Rural Development - Bhusal, Tara Prasad (Journal of Contemporary Review, 2024)
Karnali Province, in north-western Nepal, remains among the most infrastructure-constrained regions in the country despite its wealth of natural, cultural, and hydro-power potential. As of 2025, the province continues to struggle with limited road connectivity, unreliable power, digital divides, and weak social services. In this article, I reassess its development status using the latest government and donor data, focusing on transportation, energy, digital infrastructure, and social services. I examine flagship efforts like the Karnali Corridor, rural electrification schemes, and the “Digital Karnali” initiative, and assess their roles in catalysing economic transformation. I argue that coordinated, climate-resilient, and inclusive infrastructure investments, paired with strong institutions, innovative financing, and community participation, can unlock pathways to agricultural commercialization, tourism growth, renewable energy development, and rural poverty reduction. The article closes with policy recommendations and a holistic framework for sustainable rural development in Karnali and other mountainous provinces.